DETERMINATION OF RECYCLE WATER TECHNOLOGY FOR WASTEWATER TREATMENT AT UNIVERSITAS PERTAMINA AREA WITH ANALYTICAL HIRACHY PROCESS (AHP) - Hafizha Hasnaningrum; Betanti Ridhosari; I Wayan Koko Suryawan; Ariyanti Sarwono (Program Studi Teknik Sipil FT UNS, 2021)
The wastewater treatment plant (WWTP) at the Universitas Pertamina area is one of the campus's efforts to reduce the environmental impact of wastewater production. The processed WWTP can be processed into ready-to-drink water as an effort to reduce plastic waste. This plastic waste is usually produced by the consumption of mineral water products. The availability of ready-to-drink water in the campus complex is expected to increase the interest of campus residents to use tumblers and reduce the generation of plastic waste as well as university proactive efforts. The purpose of this study was to analyze the units needed to process WWTP effluent into ready-to-drink water by looking at various alternatives. This study uses the analytical hierarchy process (AHP) in determining the best alternative. The units required for each alternative are equalization tub, slow sand filter, and disinfection. Meanwhile, for processing, there are three alternatives, namely microfiltration (MF), ultrafiltration (UF), and combined microfiltration – ultra-filtration (MF-UF). The selection of these alternatives was adjusted to the criteria of cost, required membrane area, flux recovery after backwashing, and the effectiveness of total coliform removal. MF filtration technology is the largest weight, which is 0.381. Where the use of MF in the Universitas Pertamina area is cheaper and requires better area than UF and MF-UF technology.